Sociodemographic and psychological determinants of influenza vaccine intention among recipients of autologous and allogeneic haematopoietic stem cell transplant: a cross-sectional survey of UK transplant recipients using a modified health belief model. Issue 8 (8th August 2018) - Miller, Paul D E; Forster, Alice S; de Silva, Thushan I; Leonard, Hayley; Anthias, Chloe; Mayhew, Michaela; Klammer, Matthias; Paskar, Susan; Hurst, Erin; Peggs, Karl; Madrigal, Alejandro; A Snowden, John
Abstract : Objectives: Studies exploring vaccination rates among haematopoietic stem cell transplant (HSCT) recipients have focused on physician factors that limit uptake. Understanding the patient factors that determine vaccination intention is crucial to delivering a successful vaccination programme. Using a modified health belief model (mHBM), we conducted a cross-sectional survey with the objective of exploring the sociodemographic and psychological factors that determined autologous and allogeneic HSCT recipients' intention to receive the seasonal inactivated influenza vaccine (SIIV) during the 2015–2016 influenza season. Setting: The setting of our study was three tertiary level, UK National Health Service (NHS) autologous and allogeneic HSCT centres. Participants: Eligible patients were aged 16 years or over and recipients of autologous or allogeneic HSCT for any disease indication, with no absolute contraindication to receiving the SIIV during the next influenza season, and having not received the SIIV since transplant. 93 participants from 3 UK NHS HSCT centres completed an anonymous study-specific questionnaire. 78.5% were recipients of allogeneic and 21.5% autologous HSCT. Results: 23.7% of participants expressed low intent to receive the SIIV. Patients aged over 65 (OR 0.02, 95% CI 0.01 to 0.57, p=0.02) and those who had not received the SIIV prior to HSCT (OR 0.04, 95% CI 0.02 to 0.56, p=0.02) were less likely to have high intent. A multivariate logistic regression model incorporating constructs of the mHBM was statistically significant (p<0.001) and explained 74.7% of variation in SIIV intention. More patients felt that a recommendation from their HSCT team than their general practitioner would prompt them to receive the SIIV, and this was most pronounced in those who had low intent. Conclusions: The mHBM may provide a useful structure for addressing low vaccine intent among HSCT recipients and further interventional studies are warranted. We would encourage HSCT and general practitioners to discuss SIIV intention as a routine part of care.